The Role of ERP in Supply Chain Management A Comparative Study between Agricultural & Industrial Sectors - BENTALEB , Fatima Zahra; TAKI Mounaïm (Revue Internationale des Sciences de Gestion, 2022)
In today’s competitive fast-changing environment, businesses are compelled to adapt to meet customer demands and requirements. Widespread digitization of the economy reinforced use of new information and communication technologies within organizations. An effective supply chain results in enhanced financial and non-financial performance. Managers are, thus, increasingly convinced of information systems’ major role in attaining organizational objectives. Our research study aims to explain how does ERP system affect SCM performance in the agricultural and industrial sectors. It also brings to light sector specificity and its impact on enhancing and/or reducing information system performance. A total of 30 semi-structured interviews were conducted, of which 19 in a Moroccan farm group and 11 in a Moroccan industrial holding. Findings from this study explain ERP’s role in supply chain management in both sectors, and outline sector specificity’s major impact on ERP performance. Further research should examine agricultural sector particularity in countries which have reached massive advancement in information and communication technology equipment and in modernized agriculture, notably Japan, Australia and China.